Prevalence of Cryptosporidium spp. and its Association with Demographic Factors and Serum Immunological Markers in Diarrheal Patients in Kirkuk City, Iraq - Hashim, Dalia Sudad (American Journal of Biology and Natural Sciences, 2026)
Background & Objectives: Cryptosporidium spp. is a protozoan parasite that infects people with diarrheal disease globally, especially in children and immunocompromised subjects. Optimal management requires correct diagnoses and knowledge of host immune responses. The purpose of this study was to determine the occurrence of Cryptosporidium spp. to determine the prevalence of DNV among patients with diarrhea in Kirkuk, Iraq and to evaluate its associations with demographic characteristics and serum immunological markers, namely IgM, IgG, Interleukin‑6 (IL‑6), IL‑10 and IFN- γ. Materials & Methods: Stool samples from 145 diarrhea patients were screened by microscopy and serum was assayed for IgM, IgG and cytokines (IL‑6, IL‑10 and IFN-g) by ELISA method in Sunlong manufacturer. Receiver operating characteristic (ROC) curve analysis was used to identify the diagnostic accuracy, sensitivity, specificity and cutoff values. Results: The proportion of stool samples positive for Cryptosporidium was 26.2% by microscopy, 28.9% using IgM ELISA and 34.5% for IgG ELISA. It was more common among younger people aged <10 years and rural dwellers. Serum IgM, IgG, IL‑6, IL-10 and IFN‑γ levels were significantly higher in the infected patients than in the negatives (P < 0.001). According to ROC analysis, IgM and IFN‑γ were the most consistent markers (AUC, 0.82 and AUC, 0.76; respectively). Conclusions: ELISA is more sensitive than microscopy in the detection of Cryptosporidium, and combining humoral and cytokine markers gives improved diagnostic accuracy. Children and rural inhabitants are the most susceptible, and higher immune markers reveal ongoing host response to infection.